The costs to employers in Britain of workplace injuries and work-related ill health in 2005/06 - Pathak, Maniv (Sudbury, 2008)
"This paper presents detailed estimates of the costs to employers of workplace injuries and work-related ill health in 2005/06. The paper also reviews the methodology and data quality applied in past Health and Safety Executive estimates of these costs."